Ferroelectric hysteresis behavior and dielectric properties of 1-3 lead zirconate titanate-cement composites - Potong,R. (Elsevier Limited, 2015)
Lead zirconate titanate (PZT) ceramic was mixed with Portland cement (PC) to form 1-3 connectivity PZT-PC composite using a dice-and-fill technique. Ferroelectric hysteresis behavior and dielectric properties of these composites were investigated using PZT volume content of 60%, 70% and 80%. The results showed that the dielectric constant of the composite materials increased with PZT content and the dielectric constant (ε r) value is 781 for 80% PZT composite at 1 kHz. The dielectric loss tangent (tan δ) was found to decrease with increasing PZT content and the tan δ value of 80% PZT composite is 0.06. Parallel and series models were also compared to the dielectric measurement results. For the hysteresis measurements, the ferroelectric hysteresis loops can be seen for all composites. The "instantaneous" remnant polarization (P ir) was found to increase with increasing PZT content from 3.20 to 4.28 μC/cm 2 at 90 Hz when PZT volume content used was 60% and 80% respectively. © 2011 Elsevier Ltd and Techna Group S.r.l.